Peningkatan Kemampuan Berpikir Kritis melalui Analisis Film dalam Ranah Sastra - Ratu Prayuana; Diyah Iis Andriani (Pusat Riset dan Inovasi Nasional, 2023)
In Indonesia, science has been taught from an early age, starting from kindergarten to university, which emphasizes on critical thinking skills. Short film is one of the literary works in the form of audiovisual which is considered capable of helping improve students' critical thinking skills. In collaboration with the Dialectika Institute, a mass media institution engaged in civil society studies, research and development, especially focusing on the fields of religion, culture and democracy, this Community Service (PkM) activity was carried out for 3 days starting from the 22nd until February 24, 2023 which aims to improve participants’ critical thinking skills through training related to narrative and cinematographic elements in short films. In order to maximize training results, this PkM activity used several methods, including the Lecture-based Teaching style and the mentoring method in delivering training materials. In addition, the PkM team delivered questionnaires containing questions about the training material and opinions regarding the PkM to the participants in order to measure and see the results before and after the training. The results of the activity showed that this PkM activity was able to attract enthusiasm and was also able to improve the participants' critical thinking skills as seen from the results of the questionnaires delivered. In addition, this activity is able to make them see works from different perspectives than just seeing them as a means of entertainment.